MAQASHID SYARI’AH SEBAGAI SOLUSI UNTUK MENINGKATKAN PELAYANAN EKSPEDISI PADA CV. BARUMUN JAYA, MEDAN - Tongku Harapan; Eli Agustami; Nurhudawi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study is entitled "Maqashid Sharia as a Solution to Improving Expedition Service Quality at CV. Barumun Jaya Medan." The research was motivated by the importance of service quality in expedition companies, which is closely related to customer satisfaction and trust. In practice, several service-related problems were identified, including inadequate facilities and infrastructure, delays in goods delivery, ineffective handling of customer complaints, and the suboptimal implementation of Islamic values in service activities. Therefore, an approach is needed that focuses not only on company profits but also on public welfare through the implementation of Maqashid Sharia.This study aims to analyze the implementation of Maqashid Sharia in expedition services at CV. Barumun Jaya Medan, identify the factors that hinder service quality, and explain how Maqashid Sharia can serve as a solution to improve the company's services. This research employed a descriptive qualitative method with a field research approach. Data were collected through observation, interviews, and documentation involving the owner and employees of CV. Barumun Jaya. Data analysis was conducted through data reduction, data presentation, and conclusion drawing, while data validity was ensured through source and method triangulation.The findings indicate that CV. Barumun Jaya has implemented several Maqashid Sharia principles, particularly hifzh al-mal (protection of wealth) through efforts to safeguard customers' goods, hifzh ad-din (protection of religion) through the application of honesty and trustworthiness in service delivery, and hifzh al-'aql (protection of intellect) through the provision of clear information to customers. However, the implementation has not been fully optimized due to limitations in transportation facilities, inadequate operational support systems, and delays in delivery schedules. The application of Maqashid Sharia has proven to be a viable solution for improving service quality through strengthening the values of trustworthiness, responsibility, transparency, justice, and customer welfare orientation. The implementation of these principles can enhance customer trust, service quality, and the company's competitiveness in the expedition service industry.